2004
DOI: 10.1039/b315811j
|View full text |Cite
|
Sign up to set email alerts
|

Visible absorption spectra of metal–catecholate and metal–tironate complexes

Abstract: Interactions between metals and catechol (1,2-dihydroxybenzene) or other ortho-dihydroxy moieties are being found in an increasing number of biological systems with functions ranging from metal ion internalization to biomaterial synthesis. Although metal-catecholate interactions have been studied in the past, we present the first systematic study of an array of these compounds, all prepared under identical conditions. We report the ultraviolet-visible absorption (UV-vis) spectra for catecholate and tironate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
255
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(289 citation statements)
references
References 61 publications
30
255
0
4
Order By: Relevance
“…23,24) Based on those reports, silicate covering layer was not created completely and the suppression effect was lower than that of Si-Cat treated pyrite initially pH 9.5. These data also supported by Ultraviolet-visible (UV) absorption spectra studies conducted by Sever and Wilker 25) that showed that at low pH (<7), catechol is reduced and coordination complexes are dissolved instead of cross linked. Figure 5 show SEM-EDX images of 6 h Si-Cat treated pyrite samples initially pH 3, 7, and 9.5 compared with untreated pyrite.…”
Section: Effect Of Treatment Time Of Silicate Coating On Pyrite Oxidasupporting
confidence: 59%
“…23,24) Based on those reports, silicate covering layer was not created completely and the suppression effect was lower than that of Si-Cat treated pyrite initially pH 9.5. These data also supported by Ultraviolet-visible (UV) absorption spectra studies conducted by Sever and Wilker 25) that showed that at low pH (<7), catechol is reduced and coordination complexes are dissolved instead of cross linked. Figure 5 show SEM-EDX images of 6 h Si-Cat treated pyrite samples initially pH 3, 7, and 9.5 compared with untreated pyrite.…”
Section: Effect Of Treatment Time Of Silicate Coating On Pyrite Oxidasupporting
confidence: 59%
“…Thus, a key determinant of the 'mechanical homeostasis' exhibited by the cuticle may be the ability to fix the number of DOPA binding sites because it limits the number of cross-links to an acceptable range and prevents over-stiffening under high metal concentration conditions. At the same time, employing DOPA as a ligand likely facilitates the formation of very stable complexes with a broad range of metal ions [38], increasing the likelihood of filling all cross-linking sites under low metal concentration conditions. Variations in hardness, as exhibited in Al-recovery threads, are more difficult to interpret-especially because this is a viscoelastic material.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior research [49][50][51], the authors of this paper hypothesized that transition metal ions that are also strongly oxidative may cause the MAP protein chains to cross-link among themselves. Those investigations demonstrated that metal-induced cross-linking is a combination of both chelation of the metal ions by the protein and oxidation of the protein by the metal [50], and that increasing concentration of oxidative transition metals increased cross-linking of MAP protein chains [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent studies have increased the scientific community's understanding of how blue mussels cure their adhesive precursors [26][27][28][29][30][42][43][44][45][46][47][48][49][50][51], the mechanism is not yet completely understood. It appears that the precursor proteins are cross-linked by a complex interaction of dihydroxyphenylalanine (DOPA) motifs in the protein, facilitated by enzymes and oxidative reagents such as metal ions.…”
Section: Introductionmentioning
confidence: 99%